Analisa Pengaruh Motivasi terhadap Academic Burnout : Studi Mahasiswa Program Studi Manajemen Universitas Bumigora - Isra Dewi Kuntary Ibrahim; Irwan Cahyadi; Agus Hermanto; Muhammad Rahmatul Burhan (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
Students have numerous demands in education sectors, both for academic and non-academic activities to increase their soft skills including in participating for national and international competitions. Consequently, the students felt frustated with the burdens and demands leading to academic burnout. Therefore, it is needed to encouragethe students with external and internal motivationto ovaid the academic burnout. This research aims to investigate the effect of learning motivation on academic burnout (Student Study of Management Study Program at Bumigora University). Questionnaires were collected from 204 respondents of management study programs for semesters 2, 4, and 6. The data were analyzed using Partial Least Square (PLS). The research results showed that there is negative efffect on the motivation of students of the Management Study Program at Bumigora University on Academic Burnout of 46.48% but the effect is not significant.